Taman Pendidikan Al-Qur’an (TPA) Sebagai Sarana Penguatan Nilai-Nilai Keislaman: Implementasi Kegiatan Pengabdian Masyarakat Di Kampung Panyaweuyan Desa Ciherang - Hikam, Ainul; Hadi, Lalu Nuzul Ilham; Hakim, Abdul; Alamsyah, Aditya; Irfan, Muhammad (Zad Al-Ummah: Jurnal Pengabdian Masyarakat, 2025)
Community service is one form of implementation of the Tri Dharma of Higher Education which aims to provide real contributions to society. This activity is carried out by students through Al-Qur'an education at the Al-Qur'an Education Park (TPA) as an effort to improve religious literacy from an early age. The methods used in this activity include learning to read the Al-Qur'an in tartil, introduction to tajwid, and instilling noble moral values ​​in everyday life. This activity is carried out directly and participatively with an educational and communicative approach, so as to create a pleasant and meaningful learning atmosphere for children. The results of the service show an increase in the ability to read the Al-Qur'an, understanding the basics of tajwid, and positive changes in the attitudes and behavior of students. In addition to providing benefits to the community, this activity also provides valuable experience for students in applying knowledge, increasing social awareness, and building leadership. Thus, this service is a strategic step in supporting the development of a religious and character-based society.